The impact of wages and benefits systems on the performance of employees A field study in the General Company for Food Industries in the city of Baghdad - اسماعيل, معاذ غسان (Journal of Economics and Administrative Sciences, 2019)
The research aims to find out the impact of wages and benefits systems on the performance of employees, which included the research community on a sample of employees in the company, and the sample consisted of (50) employees and an employee, A questionnaire composed as prepared (23) paragraph, use the promised statistically methods in data collected by the questionnaire analysis. The research reached a number of results, the most prominent of which were: There is a correlation between wage systems, benefits and performance of employees, and the presence of the impact of the systems of wages and benefits to the performance of employees. The research was presented a set of recommendations including: increasing the effectiveness of the wage system in government institutions, and recommending to activate especially with regard to health insurance benefits systems.